Analysis of Carbon Economic Value Potential - Ahdia R. Nurlette; Muspida Muspida; Stellamaris Metekohy (Public Policy : Jurnal Aplikasi Kebijakan Publik dan Bisnis, 2024)
The study aimed to assess the potential economic value of carbon within PT Strata Pacific's IUPHHK-HA area. The methodology involved collecting, processing, and analyzing numerical data using statistical methods. Sampling techniques included stratified systematic sampling or simple random sampling, with a maximum allowable sampling error of 20%. The study found that the carbon content reserve in tree stands within PT Strata Pacific's IUPHHK area in East Seram Regency, Maluku Province, is 44.95 tonnes per hectare. Assuming a conservative carbon value of US$ 5 per tonne, the total potential economic value of tree stands and the root shoot ratio in this area ranges from US$ 12,962,231.50 to US$ 15,221,643.25. Direct benefits for the local community include improved access to agricultural and plantation roads, social management activities (CSR) by businesses, and job opportunities. These benefits are estimated to have a direct value of Rp 3,525,000,000 per year.